2021
DOI: 10.1044/2021_ajslp-20-00223
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer in a Rural U.S. Population: Quality of Life, Coping, Health Care Literacy, and Access to Services

Abstract: Purpose The aim of this study was to explore the beliefs, access, and motivations of individuals with head and neck cancer (HNC) living in a rural community in the United States, regarding their speech and swallowing deficits. Method A convenience sample of nine patient participants with HNC and nine caregiver participants completed in-depth, semistructured interviews regarding their experiences with HNC diagnosis and treatment. The researchers utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Factors such as payment/costs of treatment and services, cultural identity, socioeconomic status, education level, marital status/family support, or distance from treatment center, can not only shape a person's experience of health care but also impact their HNC outcomes 68–70 . For example, people in rural areas experience more difficulties in accessing specialist care (e.g., speech pathology) than their metropolitan counterparts 69,71 . In addition to limitations in the reporting of personal characteristics, many studies did not report crucial oncological information such as staging, disease site specifics and disease histology which makes interpretation and understanding of health care experiences challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as payment/costs of treatment and services, cultural identity, socioeconomic status, education level, marital status/family support, or distance from treatment center, can not only shape a person's experience of health care but also impact their HNC outcomes 68–70 . For example, people in rural areas experience more difficulties in accessing specialist care (e.g., speech pathology) than their metropolitan counterparts 69,71 . In addition to limitations in the reporting of personal characteristics, many studies did not report crucial oncological information such as staging, disease site specifics and disease histology which makes interpretation and understanding of health care experiences challenging.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70] For example, people in rural areas experience more difficulties in accessing specialist care (e.g., speech pathology) than their metropolitan counterparts. 69,71 In addition to limitations in the reporting of personal characteristics, many studies did not report crucial oncological information such as staging, disease site specifics and disease histology which makes interpretation and understanding of health care experiences challenging. Future studies should include oncological data to enable readers to better understand the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…Within the speech and language therapy profession, international researchers have found that people living outside of metropolitan regions face a number of barriers to service availability and accessibility (Lowe & Nobriga, 2021;O'Callaghan et al, 2005;Verdon et al, 2011;Wilson et al, 2002). Specifically in Ireland, longer waiting times have been significantly associated with decreased speech and language therapy service utilisation (Curran, et al, 2015).…”
Section: Speech and Language Therapy In Rural Areasmentioning
confidence: 99%